Hubungan Faktor Obstetri dan Sosio Ekonomi dengan Outcome Maternal Covid-19 pada Pandemi Covid-19 Gelombang Kedua di RS Rujukan Pasuruan, Indonesia - Novida Ariani; Catur Wilujeng; Syahana Aini (PT FORMOSA CENDEKIA GLOBAL, 2022)
The second wave of the Covid-19 pandemic in Indonesia has an impact on increasing maternal morbidity and mortality. Research is needed to determine maternal characteristics and their relationship to outcomes. The study design is a cross sectional at Bangil Hospital, in the second wave of covid-19 in July to September 2021. Maternal outcomes with poor results if they require treatment to fulfill oxygen (nasal cannula, hnfc or ventilator), are treated in the Intensive Care Unit (ICU), there are complications or maternal death occurs. Based on the results of the study, it was found that 26 (28.3%) mothers had good outcomes, while 66 (71.3%) had poor outcomes. Maternals requiring hnfc 6 (6.5%), were admitted to the ICU as many as 6 (6.5%). There was a significant relationship between age (p=0.036) and parity (p=0.009) with maternal outcome